Scollay Square, ca. 1920 - Unknown (Tufts Archival Research Center, 2005)
Street-level view looking southeast where Tremont and Court Streets meet Scollay Square. Automobiles and pedestrians are included in the image. The Scollay Square subway station is in the foreground of the photograph. 6 1/2 x 8 5/8 overall 7 x 9 1/8 Photographs